An intraoperative biopsy of native kidney in recipients with chronic kidney disease - S. S. Ismoilov; M. K. Gulov; S. F. Gulshanova; F. B. Mavlonov; M. M. Saymukhiddinov; Dz. M. Mugshulova (Трансплантология (Москва))
The clinically introduced intraoperative morphological study of native kidney during transplantation of kindred kidney in patients with end-stage chronic renal failure, with intact water-excretory function before dialysis, and in the period of initiating the hemodialysis sessions significantly expanded our understanding of the pathogenesis, morphological characteristics of renal parenchyma diseases, and causes of their relapses in kidney transplant.